Non-surgical correction of severe skeletal class 3 with Carriere Motion 3D class 3 - М. M. Shubitidze; T. F. Kosyreva (Эндодонтия Today)
The article describes the principle and method of treating a patient with III skeletal class malocclusion. The aim of the article is to demonstrate the treatment effectiveness with the Carriere Motion 3D class 3. As a result, Carriere Motion 3D class 3 has been shown to be effective in assessing early outcomes in the treatment of class 3 malocclusion.